Biocompatibility of a magnesium coating on a titanium surface and its effects on BMSCs. (6th December 2022) - Ni, Xiaohui; Zhao, Quanming; Pan, Xiaoyun; Zhao, Gang; Zhu, Xingyuan; Ren, Liubao; Yu, Jiong; Cai, Baisheng; Tan, Jiyang; Mi, Jingyi
ABSTRACT: Surface modification can effectively improve the biological activity of Ti, which is currently a popular research topic. In this study, we applied plasma electrolytic oxidation (PEO) technology to prepare a porous Mg-TiO2 coating on the surface of a Ti sheet. Then, we observed the adhesion and proliferation of bone marrow mesenchymal stem cells (BMSCs) on the surface of the Mg-TiO2 coating. The results showed that the Mg-TiO2 coating had a porous structure, and there was a uniform distribution of Mg on the surface and in the pores of the coating. The porous Mg-TiO2 coating showed good cytocompatibility and no obvious cytotoxicity. Significantly more BMSCs adhered to and proliferated on its surface than on pure Ti ( p < 0.05). In conclusion, a Mg-TiO2 coating with a good surface morphology and good biocompatibility and bioactivity was prepared on a Ti surface by plasma technology and may have potential for clinical applications.